"Na dnie" Maksyma Gorkiego w interpretacji polskiego teatru (na przykładzie wybranych spektakli) - Gracla, Jadwiga (Acta Neophilologica, 2024)
The subject of this sketch is a reflection on two productions of Gorky’s The Lower Depths by Leon Schiller and Krystian Lupa. The starting point for the analysis is the remarks situating Gorky’s drama within the circle of philosophical problems. In this understanding, it becomes a story about the strength and power of man, as well as the conflict between truth and lies. Despite the stereotypes regarding the perception of this drama, thanks to the successful techniques and gimmicks used by both directors, the performances created by them became the apotheosis of man. They also responded to the need of their times – the power of creation of the post-war time and the power of the dream of the present. In both cases, they managed to see and show the universal values encoded in the text, resulting in multidimensional performances that interpret Gorky’s text in a universal and timeless way.